Is AI-Powered Education Sustainable and Marketable in UK Higher Education? Exploring Opportunities and Challenges in Assessment Through the Lenses of Staff and Students - Halder, Andrina; Sultana, Saira; Hasan, Rahaman; Ahmed, Sajeel (Indian Journal of Marketing, 2025)
Purpose : This study explored the sustainability of AI-powered education in UK higher education, with a focus on its implications for assessment practices. It aimed to identify the benefits and challenges associated with integrating AI technology. Methodology : A qualitative research approach was employed, utilizing eight focus group interviews conducted with academic staff and students from two UK universities and their overseas partner institutions. The study analyzed perspectives to assess the impact of AI on teaching and assessment. Findings : The research identified significant challenges, including concerns over academic integrity, biases in AI algorithms, and the need for staff and student upskilling. However, it also highlighted opportunities such as simplified assessment workflows, improved feedback quality, and increased inclusivity through adaptive technologies. Key themes included AI usage in assessments, authenticity of AI-driven assessments, and ethical considerations. Practical Implications : The findings suggested that while AI enhanced efficiency in educational practices, its integration required careful consideration of ethical and pedagogical standards. Recommendations included developing policies and training programs to support sustainable and inclusive AI practices in higher education. Originality : This study contributed to the discourse on the future of education in an AI-driven world, emphasizing the balance between leveraging technological advancements and maintaining ethical practices. It outlined specific challenges and advantages in the context of AI’s role in assessment and educational marketing.